2001
DOI: 10.1111/j.1540-6288.2001.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Market Timing Performance of Fidelity Sector Mutual Funds

Abstract: In this paper, we test the selectivity and timing performance of the Fidelity sector mutual funds during the 1989-1998 time period. We use the S&P 500, the Dow Jones Industry Group Total Return Indexes, and the Dow Jones Subgroup Total Return Indexes as benchmarks. When we use the Dow Jones Industry benchmarks, our results indicate that many sector fund managers have positive selectivity but negative timing ability. We also find that the results are sensitive to our choice of benchmark and timing model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 17 publications
4
37
2
1
Order By: Relevance
“…Daniel and Wermers (1997) develop and apply a benchmark based on the characteristics of portfolios holdings to measure the performance of actively managed funds, and find some funds have stock selection skills. Similar results have been found for sector mutual funds by Dellva and Smith (2001), who test the stock-selection skills of funds managers using a series of industry benchmarks and conclude that many sector fund managers are skillful in picking undervalued securities. However, they also express their concern that the results are sensitive to the choice of benchmark.…”
Section: Literature Reviewsupporting
confidence: 62%
“…Daniel and Wermers (1997) develop and apply a benchmark based on the characteristics of portfolios holdings to measure the performance of actively managed funds, and find some funds have stock selection skills. Similar results have been found for sector mutual funds by Dellva and Smith (2001), who test the stock-selection skills of funds managers using a series of industry benchmarks and conclude that many sector fund managers are skillful in picking undervalued securities. However, they also express their concern that the results are sensitive to the choice of benchmark.…”
Section: Literature Reviewsupporting
confidence: 62%
“…The evidence from studies on the performance of managed funds is that only a limited number of fund managers possess market timing skills (see, for example, Treynor and Mazuy, 1966;Jensen, 1968;Kon and Jen, 1978;Henriksson and Merton, 1981;Kon, 1983;Henriksson, 1984;Admati et al, 1986;Lehmann and Modest, 1987;Lee and Rahman, 1990;Kao et al, 1998;Blake et al, 1999;Dellva et al, 2001). In the case of Australian superannuation funds, the few studies conducted on this issue have found that these funds do not possess any market timing skills at all (Prather et al, 2001;Benson and Faff, 2004;Drew et al, 2005;Faff et al, 2005).…”
Section: Brief Review Of the Literaturementioning
confidence: 93%
“…In an earlier study of Fidelity's sector funds, Dellva, DeMaskey, and Smith (2001) find positive single‐index alphas for some of Fidelity's funds. Sector funds represent only a small fraction of Fidelity's equity holdings ($17 of $413 billion in 1998).…”
Section: Introductionmentioning
confidence: 85%